Simultaneous nutrient-abundant hydroponic wastewater treatment, direct carbon capture, and bioenergy harvesting using microalgae–microbial fuel cells - Yustika Desti Yolanda; Sangsik Kim; Weonjung Sohn; Ho Kyong Shon; Euntae Yang; Sungyun Lee (Desalination and Water Treatment)
Hydroponics has increasingly been recognized as an important agricultural method due to its stable crop yields under rapidly changing environmental conditions. However, the efficient treatment of nutrient-rich hydroponic wastewater remains a major challenge. This study investigates the effect of anodic pH on the performance of microalgae–microbial fuel cells (mMFCs), focusing on bioelectricity generation, photosynthetic oxygen supply, nutrient removal and recovery, and carbon capture. The mMFC system achieved a maximum power density of 122.5 mW/m², a chemical oxygen demand removal efficiency of 93.7 %, and an anode-side total nitrogen removal efficiency of 27.5 % at an acidic anodic pH. In addition, the cathode chamber had a total ammonium nitrogen removal efficiency of 22.6 %, which was ascribed to a combination of ammonium migration and subsequent nitrogen assimilation, and a phosphate removal efficiency of 100 %, likely due to microalgal uptake and adsorption. The mMFC also effectively captured CO2 with an algal biomass yield of 0.01379 g·L−1·d−1 and a CO₂ fixation rate of 0.02528 g·L−1·d−1. These findings provide insights into the optimization of mMFCs as a sustainable solution for managing nutrient-rich hydroponic wastewater, contributing to energy-efficient and resource-recovering wastewater treatment technologies.